2021
DOI: 10.3389/fgene.2021.622724
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Microsatellite Distribution Patterns in the Genomes of Euarchontoglires at the Taxonomic Level

Abstract: Microsatellite or simple sequence repeat (SSR) instability within genes can induce genetic variation. The SSR signatures remain largely unknown in different clades within Euarchontoglires, one of the most successful mammalian radiations. Here, we conducted a genome-wide characterization of microsatellite distribution patterns at different taxonomic levels in 153 Euarchontoglires genomes. Our results showed that the abundance and density of the SSRs were significantly positively correlated with primate genome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
0
10
1
1
Order By: Relevance
“…Interestingly, it was reported that hexamers are the most abundant type of STR in intergenic, intronic and exonic regions in Srivastava et al ( 2019 ). This is in contrast with previous literature, where hexamers were typically found to be among the rarest types of STRs (Ding et al, 2017 ; Song et al, 2021 ; Willems et al, 2014 ). The way in which STR abundances were quantified may be at the root of this apparent discrepancy: Srivastava et al ( 2019 ) compared abundances of different repeat types based on the fraction of all STR bases covered by STRs of a particular motif size.…”
Section: Patterns Of Str Abundance Across Speciescontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was reported that hexamers are the most abundant type of STR in intergenic, intronic and exonic regions in Srivastava et al ( 2019 ). This is in contrast with previous literature, where hexamers were typically found to be among the rarest types of STRs (Ding et al, 2017 ; Song et al, 2021 ; Willems et al, 2014 ). The way in which STR abundances were quantified may be at the root of this apparent discrepancy: Srivastava et al ( 2019 ) compared abundances of different repeat types based on the fraction of all STR bases covered by STRs of a particular motif size.…”
Section: Patterns Of Str Abundance Across Speciescontrasting
confidence: 99%
“…Recent years have seen several comparative genomics studies aimed at investigating patterns of STR characteristics across eukaryotes at various evolutionary distances. From these investigations, we can learn that while it is true that larger genomes tend to have more and longer STRs (Ding et al, 2017 ; Song et al, 2021 ; Yuan et al, 2018 ), the STR density per megabase seems to be rather constant (Srivastava et al, 2019 ), with some exceptions noted below. Furthermore, G/C content in STRs is generally representative of the corresponding genomic G/C content, which is not correlated to the overall STR density (Srivastava et al, 2019 ).…”
Section: Patterns Of Str Abundance Across Speciesmentioning
confidence: 99%
“…AC/GT motifs were the most abundant in the dinucleotide microsatellites (Figure 1B). On the whole, the composition of the microsatellites of the S. chinensis genome was consistent with that in mammals such as humans, primates, rats, camels, and pigs [35][36][37][38][39][40]. To date, genome-wide microsatellites have been deciphered and mined for many aquatic species such as jellyfish, catfish and eel fish, etc.…”
Section: Isolation and Characterization Of Genomic Microsatellites In...mentioning
confidence: 53%
“…Our results indicate that trinucleotide repeats constitute a larger proportion of the microsatellites in the genome of Gambierdiscus australes than either monoor AC and AG dinucleotide repeats. In most eukaryotes, especially higher vertebrates such as birds and mammals, mononucleotides as well as AC and AG dinucleotides are the most common microsatellites (e.g., Song et al 2021). The exception is in green algae and some of the protists and fungi analyzed by Srivastava et al (2019), in which trinucleotides accounted for a large proportion of the motif types and were second in abundance only to hexamers.…”
Section: Discussionmentioning
confidence: 99%
“…In most eukaryotes, especially higher vertebrates such as birds and mammals, mononucleotides as well as AC and AG dinucleotides are the most common microsatellites (e.g., Song et al. 2021). The exception is in green algae and some of the protists and fungi analyzed by Srivastava et al.…”
Section: Discussionmentioning
confidence: 99%